2015
DOI: 10.1038/ejhg.2015.250
|View full text |Cite
|
Sign up to set email alerts
|

The expanding spectrum of COL2A1 gene variants IN 136 patients with a skeletal dysplasia phenotype

Abstract: Heterozygous COL2A1 variants cause a wide spectrum of skeletal dysplasia termed type II collagenopathies. We assessed the impact of this gene in our French series. A decision tree was applied to select 136 probands (71 Stickler cases, 21 Spondyloepiphyseal dysplasia congenita cases, 11 Kniest dysplasia cases, and 34 other dysplasia cases) before molecular diagnosis by Sanger sequencing. We identified 66 different variants among the 71 positive patients. Among those patients, 18 belonged to multiplex families a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…The average age at diagnosis was 5.89 years, and the sex ratio was nearly equal. Among the 18 cases of SEMD‐S collected in this review, 14 substitutions were found; c.3121G > A (p.Gly1041Ser) was reported twice …”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The average age at diagnosis was 5.89 years, and the sex ratio was nearly equal. Among the 18 cases of SEMD‐S collected in this review, 14 substitutions were found; c.3121G > A (p.Gly1041Ser) was reported twice …”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, 49 Gly substitutions occurred in the 50 missense cases, suggesting the decisive role of glycine (references are shown in Supplementary Table S1). Two intronic variants (c.2094 + 1G > A, c.2353 + 4_2353 + 7del) and two cases of gene deletion (c.2745_3221del, c.2449_2466del) also caused ACG 2 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Autosomal dominant mutations in COL1A1 are known causes of Ehlers-Danlos syndrome and osteoporosis (Steiner et al 1993;Byers 2000). Similarly, autosomal dominant mutations in COL2A1 are responsible for a number of osteochondrodysplasias (Barat-Houari et al 2016), and mutations in both COL2A1 and TRIP11 are implicated in Type 2 and Type 1A achondrogenesis, respectively. KMT2D mutations are known to be associated with Kabuki syndrome, which is characterized by cranial and facial malformations, growth deficiency, short stature, and skeletal malformations.…”
Section: Discussionmentioning
confidence: 99%